Association of BLK and BANK1 Polymorphisms and Interactions With Rheumatoid Arthritis in a Latin-American Population - Ramírez-Bello, Julian; Fragoso, José M.; Alemán-Ávila, Isidro; Jiménez-Morales, Silvia; Campos-Parra, Alma D.; Barbosa-Cobos, Rosa Elda; Moreno, José (Frontiers in Genetics, 2020)
BLK has been identified as a risk factor to rheumatoid arthritis (RA) primarily in Asian or European-derived populations. However, this finding has not been evaluated in other populations such as Latin-Americans, except for Colombians. On the other hand, BANK1 single nucleotide variants (SNVs) have been scarcely studied in RA patients. Objective. The aim of this study was to determine whether the BLK rs2736340T/C, rs13277113A/G, and BANK1 rs10516487G/A (R61H) and rs3733197G/A (A383T) polymorphisms are risk factors to RA in a sample of patients from Central Mexico. Materials and methods. We studied 957 women; 487 controls and 470 patients with RA by means of a TaqMan® SNP genotyping assay with fluorescent probes for the BLK rs13277113A/G, rs2736340T/C and BANK1 10516487G/A (R61H) and rs3733197G/A (A383T) variants. Results. The BLK rs2736340T/C and rs13277113A/G variants were associated with risk for RA: C vs T; OR 1.39, p=0.001, and G vs A; OR 1.37, p=0.004, respectively. In addition, there was also an association between BANK1 R61H and RA: A vs G; OR 1.49, p=0.003, but no with BANK1 A383T. We also identified an interaction significant between genotypes of BLK rs2736340T/C-BANK1 rs10516487G/A and RA: OR 1.65, p=0.0001. Conclusions. Our data suggest that both BLK and BANK1 confer susceptibility to RA in Mexican patients. The individual association of BANK1 rs1054857G/A with RA had not been previously reported in a particular population (except for pooled patients from several countries), therefore, our study presents the first evidence of association between this BANK1 variant and RA